THE DEVELOPMENT OF BASIC CONCEPT SCIENCE MODULE WITH SETS (SCIENCE ENVIRONMENT TECHNOLOGY SOCIETY) VISION BASED ON SCIENCE LITERACY - Arfiani, Yuni; Kusuma, Mobinta (Universitas Tanjungpura, 2019)
This study aims to determine the validity and level of readability of the Basic Concepts Science module with SETS vision (Science, Environment, Technology, Society) based on Science Literacy. Testing the validity of the module in this R D (Research and Development) uses content validity and construct validity tests, while testing the readability level of the module using the crossing test technique. The results of the study show the level of validity of the modules developed is included in the category of very high validity so that the module can be used. Meanwhile, the results of the module readability level test show that the Basic Concepts Science Module Based on Science Literacy SETS developed in the category is quite easy to understand and ideal for use in learning.